AZABORINES - AN ABINITIO STUDY - Clark, Timothy; et al. (Journal of Organic Chemistry, 1992)
Three different indicators of aromatic electron delocalization have been investigated computationally for 1,2-(3), 1,4- (4), and 1,3-azaborine (5), all of which are experimentally unknown as unsubstituted compounds. MP2/6-31G* optimizations show a varying but considerable degree of electron delocalization. The calculated order of stability (3 much greater than 4 > 5) resolves the contradictions of former reports. In contrast to the noncorrelated level, consideration of electron correlation significantly lowers the relative energy of the 1,3-isomer, for which not even substituted derivatives are known. Natural bond orbital (NBO) analyses confirm the expected Lewis structures of the 1,2- and 1,4-isomers but offer an interesting description of the intricate pi-system of 1,3-azaborine. Isodesmic equations reveal a resonance energy for 4 similar to stable Huckel aromatics and a somewhat smaller effect for 3, whereas a hyperhomodesmotic equation assigns half the resonance energy of benzene to 4. Basic differences in the sigma framework of the azaborines are considered to be responsible for the stability of 3. Computational results are supported by comparison of the scarce NMR data with chemical shifts calculated by the individual gauge localized orbitals (IGLO) method.